Immunological Study of Gastroduodenal Disorders Patients Infected with H. Pylori in Basrah Province-Iraq - Ahmed W. Al-Hilfi, Ihsan E. Alsaimary, Ali D. Al-Hilfi (Pakistan Journal of Medical & Health Sciences, 2023)
The purpose of the current study was to investigate the immunological finding of the most important Helicobacter pylori virulence factors CagA, VacA, DupA, HopQ, and IceA genotypes in gastric biopsies of gastroduodenal diseases patients infected with H. pylori, and to determine the concentrations of CagA, VacA, DupA, HopQ, and IceA in the sera of the patients infected with H. pylori in Iraq-Basrah, by using ELISA technique, to give acknowledge about the role of these virulence factors in patients with the gastroduodenal disorder. A case-control study included 112 confirmed gastroduodenal patients and 112 healthy individuals as a control group. Data about age, gender, smoking, alcohol abuse, family history, occupation, residence, and clinical findings for all study populations were collected. Blood samples have been gathered from each patient as well as the control group. Each individual in this study was examined under the supervision of a gastroenterologist and was subjected to a urea breath test (UBT) for definitive confirmation of H. pylori infection. The finding of this study show a significant effect of these factors with an increased risk of gastroduodenal disorder. Conclusion: The study show a significant effect of the studied virulence factors (CagA, VacA, DupA, HopQ, and IceA) with an increased risk of gastroduodenal disorder of Iraqi population in Basrah province. Keywords: Immunological factors, gastroduodenal disorder, Helicobacter pylori, ELISA, CagA, VacA, DupA, HopQ, and IceA.